Kompensasi dan Restitusi yang Berorientasi pada Korban Tindak Pidana - Mahrus Ali; Ari Wibowo (Universitas Airlangga, 2018)
The study proposes the compensation and restitution regulations which should be oriented to protect the victim of crime. Although most regulations have been adopted the right of the victims to receive the compensation and restitution, but this study finds that there are some weaknesses in such regulations. Hence, compensation regulation should be specifically focused on the fulfillment of the right of the victims of crime. It shall not depend on court decisions, but such compensation should be provided even though the victims ceased before the court proceeding has started, or even if he or she wrongly arrested by police. This compensation is only to cover material losses and traumatic stress recovery cost. It could be paid directly monthly/yearly and could be converted to other form of compensation. Restitution refers to the paradigm of restorative justice. In Indonesia, restitution should be based on final and binding court decision. If the perpetrator does not want to provide it for the victim, he/she has moral obligation to provide it for the victim oven without inkracht court decision, and this could be used by the judges to pardon the perpetrator. Restitution shall be enforced for all criminal offences which resulting direct and indirect losses for the victims. Restitution is not merely about monetary values but moral obligation of the perpetrator to recover the victim’s condition.